Implantação de gestão de documentos arquivísticos digitais na rede federal de educação profissional, científica e tecnológica sob o prisma da norma ISO 15489:2016 - Feitoza, Eduardo Rafael Miranda (2019)
The objective of this research is to analyze and propose requirements, guidelines, norms and standards of management of digital documents for the Federal Network of Professional, Scientific and Technological Education. The justification comes from the fact that Federal Network institutions produce and manage digital archival documents to record and prove their activities. In this sense, a theoretical reference was raised to support the objectives of the study when addressing the cultural and documentary heritage, the digital archival document and the records continuum model. The contextualization of the research situates the Federal Network institutions in the scenario of the national policy of archives, presenting the National File System, the National Archives Council and the File System Management System of the Federal Public Administration. It is a research of an applied, qualitative \ quantitative and exploratory nature, using a theoretical reference survey and a cut in the research data of the Observatory of Digital Documents held in the year 2017 to analyze the management of digital archival documents in the Network's institutions. This study concluded that there are a number of international requirements, guidelines, norms and standards, centered and related to ISO 15489, which deal with document management, system requirements, metadata and digital preservation and that these, for the most part, were addressed in Brazilian archival legislation. As an exception, we have the fact that the management of digital archival documents in business systems is not contemplated; all institutions of the Federal Network produce and manage digital archival documents in business systems. However, they do not have the structure or mechanisms to plan, implement and evaluate document management activities. Based on the conclusions of the research, a guide was applied to implement the methodology for the management of digital archival documents in the Federal Network of Professional, Scientific and Technological Education, where principles, requirements and guidelines are included for the institutions that are implementing or will implement the management of digital archival documents.